Batch microreactor for photocatalytic reactions monitoring - Danyliuk, N. V.; Tatarchuk, T. R.; Shyichuk , A. V. (Physics and Chemistry of Solid State, 2020)
Photocatalytic oxidation of organic contaminants is a hot topic in environmental research. However, an effective purification process needs an effective photoreactor. Typical light sources such as mercury and halogen lamps are replaced with more energy efficient Light Emitting Diodes. In the current work, a miniature photoreactor with low catalyst consumption was presented. The work of the micro-photoreactor is investigated using anatase and P25 industrial titania as model catalysts. The key element of the microreactor is replaceable UV-LED. The used 365 nm emission wavelength is optimal for the model pollutant Rhodamine B dye. The micro-photoreactor is able to mineralize the Rhodamine B dye almost completely.